Timing of laparoscopic cholecystectomy following ERCP and its complications: an analytical cross-sectional study from Central India - Barve, Manasi; Dhurve, Asmita (International Surgery Journal, 2026)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) followed by laparoscopic cholecystectomy represents the standard treatment for patients with choledocholithiasis associated with gallstone disease.1 However, the optimal timing of laparoscopic cholecystectomy after ERCP remains controversial. Methods: The study included 50 patients who underwent ERCP followed by laparoscopic cholecystectomy. This is an analytical cross-sectional study was conducted in the Department of General Surgery at Government Medical College and General Hospital, Nagpur, over a period of two years from January 2023 to January 2025. Patients were divided into early (within 72 hours) and delayed (6-8 weeks) groups, each comprising 25 patients. The study was conducted after obtaining approval from the Institutional Ethics Committee, and all patients provided informed consent prior to inclusion. Demographic profile, operative time, conversion to open surgery, postoperative complications, recurrent hospital visits, and duration of hospital stay were analyzed descriptively. Results: The mean age was 52.8 years with 22 females and 28 males. Mean operative time was shorter in the early group (1.4 hours) compared with the delayed group (2.1 hours). Conversion to open surgery occurred in one delayed-group patient. Postoperative complications were observed in three patients in each group, with one mortality in the early group. Recurrent hospital visits were higher in the delayed group (3.48 vs 1.92). Mean hospital stay was shorter in the early group. Conclusions: Early laparoscopic cholecystectomy following ERCP appears safe and is associated with shorter operative time, fewer recurrent biliary admissions, and reduced hospital stay without increased complications. Early surgery should be preferred whenever feasible.